(untitled) (Quinto Sol, 2013)
This paper attempts to analyze one manner of interethnic contact within the Pampas región, such as redes de rescate (“ransoming webs”): a complex web of relationships for the ransoming of captives during the 1870 and 1880 decades, among Franciscan priests, military men, Sociedades de Beneficencia, chiefs and other ranqueles, as well as renegades, captives and their families, each of them with their own motivations and conditioning factors. The work is based upon the Cartas de Frontera (Frontier Letters) kept at the “Propaganda Fide” Monastery Archive of Río Cuarto, published in 1995. It is stated that the complexity of this web does not allow to conceive either the frontier as a dividing line, or interethnic relations as binary oppositions, but rather as multi-polar relationships, that in this case, involve a wide area of connections.